Socjalny wymiar konceptu ‘PERCEPCJA WZROKOWA’ w językowym obrazie świata Rosjan i Polaków (na materiale czasowników percepcji wzrokowej) - Słupianek-Tajnert, Daria (Studia Rossica Posnaniensia, 2016)
The article discusses the social dimension of the concept of VISUAL PERCEPTION in Russian and Polish based on visual perception verbs. Similarities and discrepancies in creating the concept in both languages are indicated. The analysis takes into consideration the anthropocentric factor in forming the concept.